Does Government Spending in Health, Education, and Military Improve Welfare in Asian Developing Countries? - Wiksadana, Wiksadana; Sihaloho, Estro Dariatno (Jurnal Ekonomi & Studi Pembangunan, 2021)
The study of government expenditure is essential for economists and policymakers. This study aims to analyze the impact of various government spending, mainly on education, health, and military, on the effect of welfare on Asian Countries. This study was conducted in 20 Asian countries constructed on panel data from 2013–2017 and is analyzed using the fixed effect general least square (FEGLS) method. The results show that, government spending in health, military, and education had a positive and significant effect on Asian Countries' welfare. This research concludes that, the government health expenditure had the highest impact on welfare, followed by education and military spending.